2020
DOI: 10.3390/nu12020521
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Neuroprotective Efficacy of Palm Oil and Tocotrienol-Rich Fraction from Palm Oil: A Systematic Review

Abstract: Background: Several natural products have been reported to elicit beneficial effects against neurodegenerative disorders due to their vitamin E contents. However, the neuroprotective efficacy of palm oil or its tocotrienol-rich fraction (TRF) from the pre-clinical cell and animal studies have not been systematically reviewed. Methods: The protocol for this systematic review was registered in “PROSPERO” (CRD42019150408). This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Palm oil-derived tocotrienol-rich fraction (TRF) has been reported to provide immense protection against cytotoxicity caused by oxidative stress (OS) in rat striatal cells [ 19 ]. A recent systematic review on the safety and neuroprotective efficacy of palm-oil and TRF concluded that T3 could enhance the healthy animals’ cognitive function and attenuate OS [ 20 ]. According to Khanna et al, α-T3 exhibits cellular protection of the nerves through two main pathways: 12-lipoxygenase (LOX) and c-Src pathways [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Palm oil-derived tocotrienol-rich fraction (TRF) has been reported to provide immense protection against cytotoxicity caused by oxidative stress (OS) in rat striatal cells [ 19 ]. A recent systematic review on the safety and neuroprotective efficacy of palm-oil and TRF concluded that T3 could enhance the healthy animals’ cognitive function and attenuate OS [ 20 ]. According to Khanna et al, α-T3 exhibits cellular protection of the nerves through two main pathways: 12-lipoxygenase (LOX) and c-Src pathways [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Palm oil is the world s most commonly used vegetable oils, and present in around half of frequently used food and consumer products, from snacks to cosmetics 4) . In 2020/2021, 75 million metric tons palm oil is produced globally; Indonesia and Malaysia are the leading producers and followed by Thailand and Colombia.…”
mentioning
confidence: 99%
“…Then the risk of bias was assessed within each included study and across the whole studies. After that, any study showed more than four domains of high risks, it was excluded [ 34 ]. The appraisal of the risks of bias was implemented by two independent investigators (A.A. and M.A.A.…”
Section: Methodsmentioning
confidence: 99%